1992
DOI: 10.1039/dt9920003153
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of alkene oxidation by cationic trans-dioxoruthenium(VI) complexes. Effect of driving force on rate constants

Abstract: The kinetics of alkene oxidation by a series of isostructural trans-dioxoruthenium(vi) complexes with E0(RuV'-RuV) ranging from 0.23 t o 0.7 V vs. saturated calomel electrode has been investigated in acetonitrile. The experimental rate law is rate = k2[RuV'] [alkene]. A linear free-energy relationship between log kz and E0(RuV'-Ruv) for the oxidation of styrene and norbornene has been observed. Both steric and electronic effects of alkenes as well as the E" of the dioxoruthenium(vi) complexes affect the rate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Therefore, the observed reaction constant value is quite lower than some of the metal-oxo complexes and metalloenzymes mediated epoxidations reactions. [13,[61][62][63][64][65][66] Further,t he small negative value of the reaction constant is similar to some of the reported high-valent iron-oxo and iron(III)-acylperoxo complexes. [17,49,62] Thereafter,w eh ave carried out kinetics of the different internal olefins.W eh ave studied the second-order kinetics of cis and trans-stilbene.Itwas found that the secondorder rate constant, (k 2 % 1.12 M À1 S À1 )o ft he trans isomer is almost ten times of the cis-stilbene (k 2 % 0.141 M À1 S À1 ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the observed reaction constant value is quite lower than some of the metal-oxo complexes and metalloenzymes mediated epoxidations reactions. [13,[61][62][63][64][65][66] Further,t he small negative value of the reaction constant is similar to some of the reported high-valent iron-oxo and iron(III)-acylperoxo complexes. [17,49,62] Thereafter,w eh ave carried out kinetics of the different internal olefins.W eh ave studied the second-order kinetics of cis and trans-stilbene.Itwas found that the secondorder rate constant, (k 2 % 1.12 M À1 S À1 )o ft he trans isomer is almost ten times of the cis-stilbene (k 2 % 0.141 M À1 S À1 ).…”
Section: Resultssupporting
confidence: 86%
“…[13,[61][62][63][64][65][66] Further,t he small negative value of the reaction constant is similar to some of the reported high-valent iron-oxo and iron(III)-acylperoxo complexes. [17,49,62] Thereafter,w eh ave carried out kinetics of the different internal olefins.W eh ave studied the second-order kinetics of cis and trans-stilbene.Itwas found that the secondorder rate constant, (k 2 % 1.12 M À1 S À1 )o ft he trans isomer is almost ten times of the cis-stilbene (k 2 % 0.141 M À1 S À1 ). The higher olefin epoxidation rate of the trans-stilbene can be rationalized by the lower one-electron oxidation potential of the trans-stilbene compared to cis-stilbene.…”
Section: Resultssupporting
confidence: 86%
“…Che and co-workers have prepared a series of trans-dioxoruthenium() complexes containing macrocyclic tertiary amine ligands, 3-6 and their reactions with alkanes, alcohols and aromatic hydrocarbons have been studied. [7][8][9] These complexes are particularly suitable for kinetic studies for the following reasons. The macrocyclic ligands are resistant to oxidative degradation and ligand exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Besides porphyrins, other chelating N-donor ligands including polypyridines and macrocyclic polyamines have been used in our previous work for the oxidation of alkenes, alkanes, benzylic substrates or alcohols. Selected examples of these catalytic [71][72][73][74][75][76][77][78] and stoichiometric [79][80][81][82] oxidation systems are listed in Table 3.…”
Section: Related Non-metalloporphyrin-based Oxidation Systemsmentioning
confidence: 99%
“…In the early 1990s, we reported the stoichiometric oxidation of alkenes, C-H bonds and alcohols by oxoruthenium(V) complex [Ru V (N 4 O)O](ClO 4 ) 2 , 79 and performed kinetic studies on the alkene oxidation by trans-[Ru VI (L)O 2 ](ClO 4 ) 2 . 81 Subsequent work using the chiral oxoruthenium(IV) complex [Ru IV (PPz*)(bpy)O](ClO 4 ) 2 for alkene oxidation provided the first example of enantioselective epoxidation of unfunctionalized alkenes by an isolated chiral oxometal complex with moderate enantioselectivity. 80 It remains a challenge to perform similar studies using oxoruthenium(V) porphyrins, which are proposed as the reactive intermediate in the oxidation of…”
Section: Related Non-metalloporphyrin-based Oxidation Systemsmentioning
confidence: 99%